Geosociology, Geoanthropology, Earth System Science and the Importance of Geography in the “Anthropocene” Geosoziologie, Geoanthropologie, Erdsystemwissenschaft und die Bedeutung des Faches Geographie im „Anthropozän“ - Bätzing, Werner (Mitteilungen Der Osterreichischen Geographischen Gesellschaft, 2022)
In view of the rapidly increasing environmental problems in the Anthropocene, there are actually many new approaches in the field of sciences and humanities to strengthen the analysis of interactions between natural dynamics and human activities in the form of inter- and transdisciplinary cooperation. Because this cooperation has a strong tradition in the discipline of geography (a part belongs to sciences, another part to humanities) this article asks, if and in which manner the experiences in geography are nowadays present in the new interdisciplinary approaches. The result is negative, and this creates problems for the new approaches, because there is the danger to repeat the errors and wrong ways which have been made in the past. Therefore, it would be desirable to strengthen this geographical tradition.
CRIS-Team Scopus Importer:2024-12-16